2021
DOI: 10.1128/jvi.01832-20
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lytic Phages Protect Cells and Mice against Pseudomonas aeruginosa Infection

Abstract: With the fast emergence of serious antibiotic resistance and the lagged discovery of novel antibacterial drugs, phage therapy for pathogenic bacterial infections has acquired great attention in the clinics. However, development of therapeutic phages also faces tough challenges, such as laborious screening and time to generate effective phage drugs since each phage may only lyse a narrow scope of bacterial strains. Identifying highly effective phages with broad host ranges is crucial for improving phage therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The mixture was incubated at 37°C for 6 h. The OD600 values were measured at 20 min intervals. 36 Temperature stability of vB_PaeP_PA01EW was tested at 4 °C, 25 °C, 37 °C, 50 °C, 60 °C, 70 °C and 80 °C (pH 7.0) for 120 min. The phage titers were tested by the double-layer agar method.…”
Section: Characterization Of Vb_paep_pa01ewmentioning
confidence: 99%
“…The mixture was incubated at 37°C for 6 h. The OD600 values were measured at 20 min intervals. 36 Temperature stability of vB_PaeP_PA01EW was tested at 4 °C, 25 °C, 37 °C, 50 °C, 60 °C, 70 °C and 80 °C (pH 7.0) for 120 min. The phage titers were tested by the double-layer agar method.…”
Section: Characterization Of Vb_paep_pa01ewmentioning
confidence: 99%
“…Phages have the ability to penetrate through biofilms, which are the drug-resistant mechanisms of P. aeruginosa , and kill persistent cells ( Loc-Carrillo and Abedon, 2011 ). Phage therapies using Pseudomonas phages against P. aeruginosa infections have been proven to be successful in many cases worldwide, such as in the treatment of mouse models that were infected with the pathogen in multi-infection sites including lungs ( Debarbieux et al, 2010 ; Morello et al, 2011 ; Chen et al, 2021 ; Yang et al, 2021 ), burn wounds ( McVay et al, 2007 ), cornea ( Fukuda et al, 2012 ), gut ( Watanabe et al, 2007 ), and blood ( Watanabe et al, 2007 ; Yang et al, 2021 ). Phage therapies for P. aeruginosa infection in humans have also been reported ( Wright et al, 2009 ; Khawaldeh et al, 2011 ; Chan et al, 2018 ; Maddocks et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though phages are expected to be diluted and available in the body after administration, researchers have found that different routes of administration can lead to variable penetration in the blood (98.5% injection, 66.7% inhalation, 50% topical, and 41.1% oral) [95] due to phage filtration or potential phagocytosis. Gram-negative phage phagocytosis (Escherichia coli T2 phage) and the disintegration of phage virions [18,19,96] have been found to cause immediate reductions of phage counts in the blood after injection, as has been observed in animal models (averaging about 100-fold) [11,89,[96][97][98][99][100].…”
Section: Pharmacokinetics Of Pseudomonas Phage Therapymentioning
confidence: 99%
“…Phage therapy is primarily practiced today in parts of Eastern and Western Europe, with a research facility dedicated to phage therapeutics, the Eliava Institute, located in Tbilisi, Georgia [9]. The success of phage therapy for the treatment of P. aeruginosa infections in animals and humans has been validated in several case reports, as well as in small clinical and preclinical trials [10][11][12][13][14][15][16][17]. However, there remains much to be discovered in terms of the pharmacokinetics and pharmacodynamics (PK/PD) of phage therapy, specifically in the context of clinical applications and their role as combination therapy with antibiotics.…”
Section: Introductionmentioning
confidence: 99%